2015
DOI: 10.1016/j.chom.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunity in the Gut Selectively Targets Phenotypically Virulent Attaching-and-Effacing Bacteria for Intraluminal Elimination

Abstract: Virulence factors expressed by enteric bacteria are pivotal for pathogen colonization and induction of intestinal disease, but the mechanisms by which host immunity regulates pathogen virulence are largely unknown. Here we show that specific antibody responses are required for down-regulation of virulence gene expression in Citrobacter rodentium, an enteric pathogen that models human infections with attaching-and-effacing bacteria. In the absence of antibodies against the pathogen, phenotypically virulent C. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
166
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 34 publications
7
166
4
Order By: Relevance
“…C. rodentium resembles V. cholerae (37) in its ability to elicit a strong immune response during infection, which leads to clearance of the infection (reviewed for C. rodentium in ref. 38). Earlier work on C. rodentium (39) showed that, in otherwise germ-free mice, the organisms can colonize for up to 6 wk (the longest period tested).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…C. rodentium resembles V. cholerae (37) in its ability to elicit a strong immune response during infection, which leads to clearance of the infection (reviewed for C. rodentium in ref. 38). Earlier work on C. rodentium (39) showed that, in otherwise germ-free mice, the organisms can colonize for up to 6 wk (the longest period tested).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work on C. rodentium (39) showed that, in otherwise germ-free mice, the organisms can colonize for up to 6 wk (the longest period tested). However, colonization of the epithelial cell surface was limited to ∼2 wk, which is attributed to the development of the immune response (38). Long-term survival of the bacteria was found only in the lumen and only occurred in otherwise germ-free mice, showing that C. rodentium cannot compete with normally commensal organisms (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bifidobacteria supplementation in patients -evidence from clinical trials Disturbances in the microbiota are linked to an ever-growing number of immune-linked disease states including IBD, atopic allergy, arthritis, and obesity [80]. Therefore, there is a significant interest in treating these diseases through microbial or 'probiotic' supplementation of patients, including with Bifidobacterium.…”
Section: Other Cells Typesmentioning
confidence: 99%
“…Antiadhesin IgG antibody isotypes mediate neutrophil-dependent clearance of the enteropathogen Citrobacter rodentium from rodents (24), and in cases of ETEC and uropathogenic Escherichia coli (UPEC), antifimbrial IgGs severely limit the biomechanical resilience of CS20 and P fimbriae, respectively (25,26). This resilience is important for reducing the force on the adhesin when bacteria are exposed to shearing fluid forces in both intestinal and extraintestinal milieus (27,28).…”
mentioning
confidence: 99%